ANALISIS PELAKSANAAN PRAKERIN PADA KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF SMK - Tri Kuat; Noor Akhsan Kristiyanto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
This study aims to determine the implementation of apprenticeship in the competence of automotive light vehicle engineering expertise at SMK Muhammadiyah 1 Sukoharjo, determine the suitability of the productive abilities of students with the demands of the industrial world, and to determine the driving factors and obstacles in the implementation of the internship. This research is a qualitative descriptive study, data collection with in-depth interviews, observation and documentation, data analysis with interactive models. The informants consisted of school principals, viceprincipals, patrols, productive teachers, DUDI, and students. The results of the study are (1) the implementation he apprenticeship in the competency of automotive light vehicle engineering expertise at SMK Muhammadiyah 1 Sukoharjo covering the stages of planning, organizing, actuating and evaluating, (2) The suitability of the productive abilities of students with the demands of the business and industry world in carrying out apprenticeship is quite relevant to the competencies owned by students, (3) The driving factor that makes the implementation of internship smooth is an adequate infrastructure of school practice, good teacher performance, trusted by official workshops such as Daihatsu, Toyota, Honda, has an extensive network of internship places. The inhibiting factor is that there are still some students who have poor practice places, there are some students who are less able to adjust to the work environment.